Efektivitas Pembelajaran Berbasis Masalah Terhadap Kemampuan Berpikir Tingkat Tinggi Siswa pada Materi SPLTV Kelas X SMA - Situmorang, Mahanda Dinaria; Tambunan, Hardi; Sihombing, Dame Ifa (Universitas PGRI Semarang, 2026)
This study was conducted to determine the effectiveness of implementing problem-based learning (PBL) on students’ higher-order thinking skills regarding SPLTV material in 10th grade at State High School 17 Medan during the 2025/2026 academic year. This study is a quantitative study using a one-shot case study design. The population in this study consists of all 10th-grade students at State High School 17 Medan, comprising 9 classes, and the sample consists of classes 10-8 and 10-9, selected using purposive sampling. The instruments used in this study include tests, questionnaires, and observation sheets, all of which were first tested for validity and reliability. The effectiveness of learning was assessed based on effectiveness indicators, namely the systematic structure of instruction, teacher communication, student response, student activity, and criteria for the achievement of learning objectives. Data from each indicator instrument in this study were analyzed using descriptive analysis with the aid of frequency distribution tables and tables of criteria for the achievement of learning objectives. The results of this study indicate that all five indicators—namely, the systematic nature of learning—met the “good” category; teacher communication met the “good” category; student responses and student activities met the “good” category; and learning objectives were achieved. Based on these five indicators, the effectiveness of learning also met the “good” criteria. Consequently, problem-based learning aimed at developing higher-order thinking skills in the SPLTV curriculum is effective and falls into the high category.